Bifarie itaque potest legi: Ambivalent Exegesis in Ælred of Rievaulx's De Oneribus - White, Lewis (Cistercian studies quarterly, 2007)
The article focuses on the exegetical approach of the monk Ælred of Rievaulx regarding the wickedness in Babylonia and the righteousness of Israelites. He often used the strategy In Adventu Domini during his sermon to signify that Babylon has the world of covetousness. According to him, the best example of love to unite the creatures who lived in heaven and earth is the Incarnation.